Study of Potential α-Glucosidase Inhibitor from Tithonia diversifolia: In Vitro, Pharmacokinetics, Toxicology, and Molecular Docking - Alfarado, Daniel; Shiyan, Shaum; Ferlinahayati, Ferlinahayati (Universitas Gadjah Mada, 2025)
The kipahit plant (Tithonia diversifolia) is commonly used in traditional medicine to treat various diseases, particularly diabetes. Investigating the bioactive compounds of T. diversifolia as α-glucosidase enzyme inhibitors is very promising to be carried out for antidiabetic drug development. A combination of in vitro and in silico studies was conducted to determine the inhibitory interaction of these compounds. In vitro assay was performed using the spectrophotometry method on methanol extracts and revealed that the stems (IC50 = 105.0 ppm) exhibited higher bioactivity than the leaves (IC50 > 500 ppm). Metabolite profiling of the methanol extract of the T. diversifolia stems revealed 94 compounds, which continued for in silico methods (pharmacokinetics and toxicology, followed by molecular docking with flexible-rigid method) for antidiabetic activity and drug-likeness parameters. Among the identified compounds, eight showed promise as drug candidates for inhibiting the α-glucosidase enzyme. The compound 1-(7-hydroxy-2-(hydroxymethyl)-2-methyl-2H-chromen-6-yl)ethanone was the most effective candidate among the eight candidates, based on its high similarity liked positive control, the lowest binding affinity value (−7.739 kcal/mol), and the inhibition constant (97.0 μM). The research findings suggested that the compounds in T. diversifolia had the potential to inhibit the α-glucosidase enzyme and could be developed into antidiabetic drugs.